Konsep Pemikiran Al-Farabi dan Relevansinya dengan Pendidikan Agama Islam: (Studi Kasus di SMKN 3 Kota Bekasi) - Gawi Yulianti; Nurhayatin; Iyad Suryadi; Helmawati (PT. Pusmedia Group Indonesia, 2024)
According to Al-Farabi education is a means of acquiring a series of values, knowledge and skills. According to Al-Farabi, Islamic education must emphasize the formation of morals and reason. The use of reason to acquire knowledge must be accompanied by the development of good morals or character. The purpose of this writing is to find out the background of Al-Farabi's biography, life and thoughts regarding Al-Farabi's education with Islamic education in this modern era and how it is relevant to the concept of Islamic religious education (PAI) at SMAN 3 Bekasi City. The method used is descriptive qualitative method. Researchers collected data sources through text literature, both books, journals, and articles and interviews, observations related to this discussion. The research results show that Al-Farabi was a Muslim philosopher and scientist who mastered various fields of science and language. According to Al-Farabi, educational thinking is to prioritize the formation of morals. According to Al-Farabi, knowledge is clean, and can only be obtained by people who have a clean heart and good morals. In the educational process, according to Al-Farabi, a student must pay attention to every difference in the potential of the student. There is relevance to the religious education implemented at SMAN 3 Bekasi City in the form of moral education and the formation of good morals through religious spiritual habits. Keywords: Al-Farabi; Moral Thinking; Islamic Religious Education